Evidences of the influence of the detonation sequence in rock fragmentation by blasting – Part II - Cardu,Marilena (2015)
Abstract This paper shows the work conducted at the Experimental Mine of the Research Center of Responsible Mining of the University of São Paulo, taking into account the theoretical issues presented in the first part of the article. The research was performed without changing the production cycle and without resorting to investments in new types of equipment: it has attempted to increase the productivity of the quarry, by lowering production costs and improving the quality of the product. Some Key Performance Indicators (KPIs) were established to monitor the results. A new blast design method, a more appropriate initiation sequence and some simple, inexpensive and effective solutions were identified and applied. The results show that the proper selection of delay timing can be of significant benefit to downstream processes as well as enhanced fragmentation itself.